2022
DOI: 10.3390/en15030859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Intercalation and Dispersion of Organoclays on Energy Demand in the Extrusion of Recycled HDPE/PP Nanocomposites

Abstract: Few studies have drawn on any systematic research into the energy demand to produce polymer-based nanocomposites. Regarding the problem, it is well-known that single screw extrusion is an energy-intensive process, so the incorporation of energy meters must be considered to examine the energy efficiency of the process. In this study, the effect of a nanoclay addition on the energy demand of the extrusion process was examined by extruding recycled high-density polyethylene (rHDPE) and recycled polypropylene (rPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…RH has been observed to increase the thermal stability of the polymer matrices [15] due to its insulating properties. It has been observed that inorganic materials can decrease the melting temperature of polyolefin single extrusion process [38], so RH was able to reduce the stock temperature in these rHDPE polymer composites.…”
Section: Torque Rheometry and Processability Analysismentioning
confidence: 99%
“…RH has been observed to increase the thermal stability of the polymer matrices [15] due to its insulating properties. It has been observed that inorganic materials can decrease the melting temperature of polyolefin single extrusion process [38], so RH was able to reduce the stock temperature in these rHDPE polymer composites.…”
Section: Torque Rheometry and Processability Analysismentioning
confidence: 99%